HUBUNGAN ANTARA PERILAKU MENONTON SINETRON PERCINTAAN DENGAN PERILAKU PACARAN PADA SISWA- SISWI YAYASAN ISLAMIYAH DI SMA ETHIKA PALEMBANG - Vusvi Eka Sari Zendrato; Muhajirin Muhajirin; Kiki Cahaya Setiawan (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2016)
Courtship behavior is a series of joint activities tinged intimacy (such as a sense of ownership and self-disclosure) as well as their emotional attraction between men and unmarried women with the aim to know each other and see the fit between one another consideration before marriage, but also many dents student doing courtship behavior on the grounds of the main factors to watch soap operas frequent lovemaking makes bad influence on students. Behaviour love to watch soap operas is how seringkan activities using the eye or looking at television or watch a soap opera soap opera featuring romance. This study aims to test empirically whether there is a relationship between the behavior of watching soap opera romance with dating behavior. Behaviors to watch soap operas romance dalah independent variable, while the dependent variable is a courtship behavior. The hypothesis is